The Type and Number of Expeditions in the Franklin Search, 1847-1859 - Ross, W. Gillies (ARCTIC, 2002)
Forty-nine books and articles published during the last 140 years give two dozen different figures for the number of expeditions that participated in the search for Sir John Franklin (1847-59). The figures range widely, from 17 to more than 70. According to the classification of expeditions presented here, 20 search expeditions, 11 supply expeditions, and one relief expedition (a total of 32) were directly involved in the Arctic search, and four bi-purpose expeditions contributed in some way, making a total of 36. Three aborted search expeditions failed to reach the Arctic. Quarante-neuf livres et articles publiés au cours des derniers 140 ans donnent une vingtaine de chiffres différents pour le nombre d'expéditions ayant participé à la recherche de sir John Franklin (1847-59). Les chiffres varient très largement, allant de 17 à plus de 70. Selon la classification des expéditions présentées ici, 20 expéditions de recherche, 11 expéditions de ravitaillement et une expédition de relève (total de 32) sont intervenues directement dans la recherche effectuée dans l'Arctique, et quatre autres expéditions à double mandat y ont également participé d'une manière ou d'une autre, ce qui fait un total de 36. Trois expéditions de recherche interrompues n'ont pas réussi à atteindre l'Arctique.